2022
DOI: 10.1097/aog.0000000000004646
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Removal of Midurethral Sling in Women Undergoing Surgery for Presumed Mesh-Related Complications

Abstract: To assess whether some, or all, of the mesh needs to be removed when a midurethral sling is removed for complications.DATA SOURCES: A systematic review and meta-analysis was conducted. MEDLINE, Cochrane, and ClinicalTrials. gov databases from January 1, 1996, through May 1, 2021, were searched for articles that met the eligibility criteria with total, partial, or a combination of anti-incontinence mesh removal. METHODS OF STUDY SELECTION:All study designs were included (N$10), and a priori criteria were used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…However, it is lower when compared with other series of complete removal, in which up to 69% have been reported 19,21 . Indeed, a recent systematic review concluded that the risk of post‐operative SUI is lower after partial mesh removal compared to total (odds ratio 0.46, 95% CI 0.22–0.96) 22 . This must be balanced with the potential risk of the initial symptom persistence in case of partial removal.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, it is lower when compared with other series of complete removal, in which up to 69% have been reported 19,21 . Indeed, a recent systematic review concluded that the risk of post‐operative SUI is lower after partial mesh removal compared to total (odds ratio 0.46, 95% CI 0.22–0.96) 22 . This must be balanced with the potential risk of the initial symptom persistence in case of partial removal.…”
Section: Discussionmentioning
confidence: 92%
“… 19 , 21 Indeed, a recent systematic review concluded that the risk of post‐operative SUI is lower after partial mesh removal compared to total (odds ratio 0.46, 95% CI 0.22–0.96). 22 This must be balanced with the potential risk of the initial symptom persistence in case of partial removal. Post‐operative bothersome urgency was reported in 37% of the patients, which differs significantly from a series that reported an increase in urgency after total mesh removal in 80%.…”
Section: Discussionmentioning
confidence: 99%
“…This makes sense, as the endoscopic procedure, in this case, breaks the continuity of the sling, and therefore these women would be expected to have a higher risk of incontinence (one of the components of the UDI‐6 score). A recent systematic review identified a higher risk of stress incontinence after complete sling removal compared to partial transvaginal removal, 17 therefore it is reasonable that endoscopic resection (representing the smallest possible partial removal) would minimize this risk for women. Fourth, most of the previous reports of endoscopic management of urinary mesh extrusion have focused on mesh within the bladder, and a small series suggested that treatment of intraurethral mesh extrusion may not have satisfactory results compared to intravesical mesh extrusion (33% vs. 80% anatomic success respectively) 18 .…”
Section: Discussionmentioning
confidence: 99%
“…163 A recent systematic review found no difference between partial or total mesh removal regarding improvement in pain outcomes, with a postoperative risk of recurrent SUI lower with partial vs. total mesh removal. 165,166…”
Section: How Should Pain After Transvaginal Mus Be Investigated and M...mentioning
confidence: 99%
“…176,177 Transvaginal mesh removal and urethral repair is an alternative treatment approach that is likely associated with more potential morbidity and a higher risk of post-procedure stress incontinence. 165,178 To lessen morbidity, a staged primary endoscopic excision/release may be considered prior to open transvaginal excision. In most cases, management of this complication should be referred to an appropriate specialist with experience managing transvaginal mesh complications.…”
Section: What Is the Risk Of Mesh Exposure In The Urinary Tract After...mentioning
confidence: 99%